A One-year COVID-19 Pandemic Effect on the Orthopaedic Field in Indonesia: A Cross-sectional Multi-center Study - Utomo, Pamudji; Haridhi, Abdurrahman Afa; Yudistira, Mochammadsyah Beizar (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The World Health Organization announced the COVID-19 outbreak as a global pandemic on March 11, 2020. Despite the fact that orthopedists are not considered front-line staff in the fight against the pandemic, the pandemic has had an enormous impact on orthopedics daily practice. A few studies have looked at the pandemic effect on the orthopedics field, but none have looked at the impact of a 1-year pandemic, especially in Indonesia. MATERIALS AND METHODS: This cross-sectional multi-center study was conducted at seven tertiary referral hospitals in Indonesia. Through hospital medical records, data were collected for a year, starting from the month the Indonesian government announced the first case of COVID-19 (March 2020–February 2021) and compared to data from the year before COVID-19 as a control (March 2019–February 2020). In addition, the researchers analyzed the number of patients in the emergency room (ER), outpatient clinic, inpatient, and operating room. RESULTS: Overall, the number of orthopedic patients in the ER declined by 44% from 11.053 to 6.139 patients during the 1st year of the pandemic, with 28 patients reported as getting COVID-19. The outpatient clinic decreased by 34%, from 10.9780 to 72.200 patients, with two confirmed cases. Furthermore, the inpatient unit decreased from 15.365 to 9.526 patients, a 38% decrease, with the highest recorded case confirmed at 78 patients. The last, with 73 confirmed, showed a 27% reduction in OR from 12.954 to 9.431 patients. CONCLUSION: In this study, analysis on the effect of the COVID-19 pandemic on the field of orthopedics in seven tertiary referral hospitals in Indonesia shows a significant decrease almost in all units. LEVEL EVIDENCE: III, Cross-sectional multi-center study.